Industrial accidents / Hassan Alias and Nik Abdul Haleem Izzuddeen Nik Ibrahim - Alias, Hassan; Nik Ibrahim, Nik Abdul Haleem Izzuddeen (1993)
Industrial accident is a major problem faced by the top industrial managements. Studies indicate that safe plants are efficient plants, and to a large extent, safety promotes productivity. Managements even have begun to realize that the safety of employees while off the job is also important to an enterprise. Notice how many of the indirect costs may be incurred as a result of nonworking accidents. Inefficiencies resulting from temporary replacements and lowered effectiveness of the workers after the accident do not depend on where or when an injury is suffered. Even where employees were not paid for the days absent from the job due to illness, absenteeism can cost the fmn considerable sum of money.